Automated extraction of standardized antibiotic resistance and prescription data from laboratory information systems and electronic health records: a narrative review - Cappello, Alice; Murgia, Ylenia; Giacobbe, Daniele Roberto; Mora, Sara; Gazzarata, Roberta; Rosso, Nicola; Giacomini, Mauro; Bassetti, Matteo (Frontiers in Antibiotics, 2024)
Antimicrobial resistance in bacteria has been associated with significant morbidity and mortality in hospitalized patients. In the era of big data and of the consequent frequent need for large study populations, manual collection of data for research studies on antimicrobial resistance and antibiotic use has become extremely time-consuming and sometimes impossible to be accomplished by overwhelmed healthcare personnel. In this review, we discuss relevant concepts pertaining to the automated extraction of antibiotic resistance and antibiotic prescription data from laboratory information systems and electronic health records to be used in clinical studies, starting from the currently available literature on the topic. Leveraging automatic extraction and standardization of antimicrobial resistance and antibiotic prescription data is an tremendous opportunity to improve the care of future patients with severe infections caused by multidrug-resistant organisms, and should not be missed.